SISTEM PAKAR DIAGNOSIS GANGGUAN JIWA BERBASIS WAP (Information Technology and Telematics, 2012)
In everyday life mental disorders commonly experienced by many people, but are often considered to be a normal state. So the role of the psychologist and physician is required. The presence of psychologists away from the community became an obstacle in overcoming mental disorder that occurs in society. Expert systems are systems that try to adopt human knowledge into a computer that is designed to model the ability to solve problems like an expert. The purpose of this study is to provide a convenience for the public to know the nature of mental disorders in a person, and their treatment should be done. The database and knowledge base in accordance with the guide book PPDGJ-III that has a proper analysis of the results Keywords: Expert System,Mental Disorders, WAP